2014
DOI: 10.1007/s12206-014-0847-2
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation of temperature distribution and flooding phenomena of cathode flow fields in a proton exchange membrane (PEM) fuel cell

Abstract: Water management is considered to be one of the main issues to be addressed for the performance improvement of proton exchange membrane (PEM) fuel cells. In this paper, to investigate cathode flooding and its relationship with temperature distribution, an experimental study was carried out on cathode sides of an operating single PEM fuel cell. For the direct visualization of temperature fields and water transport in cathode flow channels, a transparent cell was designed and manufactured using quartz window. Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…They reported that the enthalpy of condensation is the cause for an elevated temperature in areas where liquid water is observed. Kim et al [20] performed a similar investigation to that of Hakenjos et al [19] and reached to the same conclusion, i.e. the enthalpy of condensation is the cause for the high temperatures in the areas where liquid water is observed.…”
Section: Introductionsupporting
confidence: 54%
“…They reported that the enthalpy of condensation is the cause for an elevated temperature in areas where liquid water is observed. Kim et al [20] performed a similar investigation to that of Hakenjos et al [19] and reached to the same conclusion, i.e. the enthalpy of condensation is the cause for the high temperatures in the areas where liquid water is observed.…”
Section: Introductionsupporting
confidence: 54%
“…It is questionable if robust temperature control is always implemented effectively in reported studies, and in any case, there is likely to be a distribution of current density and temperature within cells such that true isothermal operation is exceedingly difficult to achieve. In practice, for technological systems, fuel cell temperature will vary across the polarisation curve range [1][2][3][4] when exposed to dynamic operation and during start-up [5]. Temperature will be heterogeneously distributed across cells and throughout stacks and is a complex function of reactant flow [6], current density distribution [7,8], flow-field design [9,10], cooling mechanism [11,12], etc.…”
Section: Introductionmentioning
confidence: 99%